Case Studies in Global Health (Taylor & Francis, 2026)
The field of Global Health can be complex and challenging to navigate. This fascinating set of case studies not only illustrates the global interconnectedness of health issues across different continents but also brings clarity to the range of social theories used to make sense of the construction and distribution of health and illness around the world. Each chapter features an ethnographic case study paired with a social theory. Beginning in southern Mexico, and exploring the concept of structural violence through the story of a family diagnosed with HIV and TB, the book travels to Haiti to add a postcolonial analysis through the story of a young boy with a congenital heart condition. Heading north to Navajo Nation, the volume explores ideas of cultural competence and biopower through the story of a trans woman seeking care, and travels to the other side of the globe to illuminate structural competency through a case focused on digestion in central India. The final case, set in the hills of Nepal, centers on the experience of healthcare providers navigating changing health and social norms, through the framework of social suffering. Both accessible and engaging, this volume will be important reading for students and scholars of medicine and public health, medical anthropology and sociology, and development studies, as well as professionals working in global health. The Open Access version of this book, available at http://www.taylorfrancis.com, has been made available under a Creative Commons Attribution-Non Commercial-No Derivatives (CC BY-NC-ND) 4.0 license.